Subcutaneous Reaction of Rat Tissues to Nanosilver Coated Gutta-Percha - Mozayeni, Mohammad Ali; Dianat, Omid; Tahvildari, Shahin; Mozayani, Maryam; Paymanpour, Payam (Iranian Endodontic Journal, 2017)
Introduction: Gutta-percha (GP), is a neutral and non-toxic material. The aim of this animal study was to compare the biocompatibility of nanosilver coated GP (NS-GP) with conventional GP in subcutaneous tissues in a rat model. Methods and Materials: Conventional GP and NS-GP were subcutaneously implanted in the backs of 20 male Wistar rats (n=10). A control animal was assigned for each trial period. Ten animals were sacrificed after 7 and 30 days and light microscopic evaluation of tissue reaction to NS-GP (n=20) and conventional GP (n=20) was accomplished. The Mann-Whitney U, Wilcoxon Signed Ranks, Fisher Exact, and McNemar tests were used for statistical analysis of the data. Results: After 7 days, inflammation was moderate and mild for NS-GP and conventional GP, respectively (P<0.001). After 30 days, no inflammation was discernible in conventional GP. However, mild inflammation was reported for NS-GP (P<0.001). Regarding inflammatory cell type, there was a significant difference between two experimental groups at both times (P<0.001). Conclusion: Inflammation decreased over time in both groups. Fibrous connective tissue, a representative of healing and control of inflammatory process, surrounded both test materials. NS-GP was biocompatible and might be a reasonable endodontic obturation material. Keywords: Gutta-Percha; Inflammation; Nanosilver Coated Gutta-Percha; Subcutaneous Connective Tissues